A motion capture protocol for the kinematic analysis of transfemoral and transtibial sprinters - Di Marco, Roberto; Breban, Samira G.; Zullo, Giuseppe; Gariboldi, Francesca; Scapinello, Mattia; Migliore, Gian Luca; Petrone, Nicola; Cutti, Andrea G. (Frontiers in Bioengineering and Biotechnology, 2025)
Optimizing performance and safety in sprinters with lower-limb amputation requires standardized methods. This study presents a novel marker-based motion capture protocol to define local coordinate systems and Cardan sequences for in-vivo analysis of running biomechanics in athletes with transfemoral (TF) and transtibial (TT) amputation. The protocol provides detailed definitions and shares computational codes, supporting prosthetists and coaches in optimizing prosthetic setups. Moreover, integrating in-vivo biomechanics data into in-vitro and in silico experiments could lead to safer, more effective prosthetic designs. The methodology was tested involving two Paralympic gold medallists (one TF, one TT). To support global adoption and broad validation, all necessary computational tools, including kinematic calculation codes and model configuration files, are openly provided. These resources enable researchers to apply the protocol to various prosthetic setups and further test its applicability. By fostering global collaboration, this work lays the foundation for analysing Paralympic sprinting, optimizing athletic performance, improving prosthetic design, and advancing Paralympic sports biomechanics.